2004
DOI: 10.3732/ajb.91.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between molecular markers and adaptively significant genetic variation in Bromus tectorum (Poaceae), an inbreedingannual grass

Abstract: Single sequence repeat (SSR) and amplified fragment length polymorphic (AFLP) molecular marker genotypes in cheatgrass (Bromus tectorum) were compared to published data on phenotypic variation in seed dormancy, vernalization requirement, and resistance to the pathogen Ustilago bullata. Several features of cheatgrass facilitated this study: it is a recent invader in the western United States, has considerable phenotypic polymorphism, and is an obligate self-pollinator. Forty self-pollinating lines from four pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 44 publications
2
38
3
1
Order By: Relevance
“…Moreover, our findings are congruent with those of previous allozyme study [7] showing that the proportion of the genetic diversity that resides between populations (G ST = 0.53) was far higher than reported for most diploid plants and were only comparable with the mean G ST reported for obligatory selfing species [78]. For example, a large reduction of genetic variability within populations and increased differentiation between populations have been observed in obligatory selfing grass Bromus tectorum [80] or in predominantly selfing grass Nassella pulchra [81] and in wetland species Typha latifolia [82].…”
Section: Genetic Distinction and Diversity Of Melica Ciliata And M Tsupporting
confidence: 79%
“…Moreover, our findings are congruent with those of previous allozyme study [7] showing that the proportion of the genetic diversity that resides between populations (G ST = 0.53) was far higher than reported for most diploid plants and were only comparable with the mean G ST reported for obligatory selfing species [78]. For example, a large reduction of genetic variability within populations and increased differentiation between populations have been observed in obligatory selfing grass Bromus tectorum [80] or in predominantly selfing grass Nassella pulchra [81] and in wetland species Typha latifolia [82].…”
Section: Genetic Distinction and Diversity Of Melica Ciliata And M Tsupporting
confidence: 79%
“…Elymus caninus (Díaz et al 1999) or Elymus alaskanus (Sun et al 2002), but comparable with the level of genetic variation found in obligate self-pollinators, e.g. Bromus tectorum (Bartlett et al 2002;Ramakrishnan et al 2004) or in the self-compatible Calamagrostis porteri subsp. insperata (Esselman et al 1999).…”
Section: Level Of Aflp Variation: Implications For the Breeding Systementioning
confidence: 90%
“…Because the visualization in the current study was carried out on a different machine than the one used in our original studies (a Perkin-Elmer ABI 377 automated DNA analyzer), we included DNA from a set of B. tectorum reference lines from the earlier study (Ramakrishnan et al 2004) along with the 200 unknowns, to verify that the two DNA analyzers gave identical allele lengths for each of the SSR markers. We encountered small but consistent differences in allele lengths at each locus for reference lines from the two analyzers.…”
Section: Molecular Genetic Characterizationmentioning
confidence: 99%
“…Because of its highly selfing breeding system, it is possible to associate B. tectorum SSR genotypes with particular suites of adaptive traits (Ramakrishnan et al 2004). There is also some support for the hypothesis that pre-adapted inbreeding lines with characteristic SSR marker fingerprints are favored by selection in similar environments over a wide geographic range (Ramakrishnan et al 2006).…”
Section: Introductionmentioning
confidence: 95%